Analisis Implementasi Corporate Social Responsibility Pada Perusahaan Berlabel Syariah di Bursa Efek Indonesia - Ferry Khusnul Mubarok (Trunojoyo University of Madura, 2019)
This study aims to identify the implementation of the Corporate Social Responsibility of Sharia Labeled Companies on the Indonesia Stock Exchange. This study uses a quantitative descriptive approach. The sample of this study is a sharia-labeled company listed on the Indonesia Stock Exchange, using a purposive sampling method. The results showed that the implementation of a sharia-labeled Corporate Social Responsibility company listed on the Indonesia Stock Exchange from 2009 to 2012 fulfilled all CSR disclosure indicators based on the Global Initiative Reporting. Companies labeled sharia express 6 aspects of CSR disclosure that cover economic, environmental, labor, human rights, social and product aspects.